Efectividad a corto plazo de la vacuna antipertusis en adolescentes : revisión sistemática (2015)
Introduction In recent years, there has been an increase in the number of cases of pertussis, predominantly affecting infants under one year of age, teenagers and adults. In 2005, the Advisory Committee on Immunization Practices of the United States (ACIP) recommended administering a booster shot of acellular pertussis-containing vaccine for teenagers, a strategy adopted by various countries. Our objective was to perform a systematic review of the short-term effectiveness of this preventive strategy. As far as we know, this review has not been performed to date. Methods A systematic literature review of publications in English and Spanish on the short-term effectiveness of a reduced antigen content diphteria-tetanus-acellular pertussis vaccine (Tdap) as a booster shot for teenagers, between January 1990 and December 2012. Results An initial search revealed a total of 121 results; of 26 papers preselected, 4 were included in the review. They were classified as level of evidence Ib. The immunogenicity against tetanus and diphtheria was tested with the Tdap vaccine versus tetanus, reduced diphtheria (Td). The authors found that the immune responses were significant and similar. The responses to the Tdap against specific antigens of Bordetella pertussis, diphtheria and tetanus were appropriate and significant. The reactogenicity was low, and the most common local adverse event was pain, predominantly in the group that received Tdap. Conclusions Available evidence supports the strategy of using Tdap vaccine as a booster in teenagers from 10 to 18 years of age. This conclusion is based on its low reactogenicity and its adequate immunogenicity against tetanus, diphtheria and Bordetella pertussis. © 2014 ACIN. Published by Elsevier España, S.L.U. This is an open access article under the CCBY-NC-ND license.